423 Prevalence and prognostic significance of atrial arrhythmias in arrhythmogenic cardiomyopathy. (8th December 2021) - De Luca, Antonio; Cappelletto, Chiara; Romani, Simona; Perotto, Maria; Gregorio, Caterina; Barbati, Giulia; Stolfo, Davide; Merlo, Marco; Sinagra, Gianfranco
Abstract: Aims: Limited data are available concerning atrial arrhythmias (AA) role in arrhythmogenic cardiomyopathy (AC). The aim of the present study was to assess the prevalence and incidence of AA in a large cohort of AC patients and to evaluate its association with clinical outcomes. Methods and results: We retrospectively analysed 115 patients with definite diagnosis of ARVC, according to 2010 Task Force Criteria, enrolled in the Trieste Heart Muscle Disease Registry. Subjects were further classified into two phenotypic variants, based on ventricular involvement: right-dominant and biventricular form. Uni- and multivariable, extended Kaplan-Meier and cumulative incidence function analysis were performed, as appropriate, for the primary composite endpoint of death and heart transplant (HTx) and for the two distinct secondary endpoints of: (i) death, HTx and first heart failure (HF) hospitalization; (ii) first major ventricular arrhythmias (MVA). Mean age of patients at the time of enrollment was 39 ± 16 years and 80% were male. 73 patients (63%) had a right-dominant form, while 42 (37%) presented a biventricular involvement. AA occurred in the 26% of our study population at baseline or during a median follow-up of 214 months (IQR: 105–311), with a non-significant trend in higher cumulative incidence of AA in patients with biventricular form. At baseline, patients experiencing AA were older (44 ± 18 vs. 37 ± 15 years, P  = 0.044) and had larger atrial dimensions, in particular of the right atrium (RA) (23, IQR: 19–27 vs. 18, IQR: 15–25 cm 2, P  < 0.007). AA emerged as independently associated to death/HTx (HR 2.68, 95% CI: 1.02–7.05, P  = 0.046) along with NYHA class >2 (HR: 7.08, 95% CI: 2.50–20.1, P  < 0.001) and RA area (HR: 1.05, 95% CI: 1.01–1.09, P  = 0.011). Consistently, AA were also independently associated with the secondary endpoint of death/HTx/HF hospitalization (HR: 2.50, 95% CI: 1.06–5.88, P  = 0.036), together with NYHA >2, the presence of biventricular involvement, higher RA and left atrium area. Finally, AA did not emerge as independently correlated to MVA during follow-up. Conclusions: This observational long-term study suggests that AA were common in patients with AC and were independently associated with poor outcomes, mostly related to HF events. A prompt identification throughout the follow-up of AA appears relevant in improving the clinical management of AC patients.